Desain Pembelajaran Pendidikan Agama Islam Berbasis Scientific-Cum-Doctriner Untuk Membentuk Karakter Religius Dan Kreatif Di Sdn Rejowinangun 1 Yogyakarta - Adhika Alvianto (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
The age of the students in primary school is at the concrete operational phase. A child at the concrete operational stadium is able to think operationally with a condition that his or her thinking material is in a concrete manner. Thus, it needs a research to figure out how the learning design is to build the religious and creative character. This research is conducted using the qualitative subject and object taking the background of State Primary School of Rejowinangun 1 Yogyakarta. The data was collected by means of observation, interview and documentation. The data analysis was conducted by defining the data collected and then a conclusion is made. The data validity was examined through the triangulation technique. The result of the research showed that the learning design of scientific-cum-doctriner-based Islamic education started from the need analysis of the student, objective design, materials, steps, sources and learning evaluation. The building of religious and creative character can result in: the habit to say salaam (greeting), doing a frugal behaviour as taught by the Prophet of Muhammad SAW, able to read the short Qur’an verses before starting to study, doing Shalat in congregation, doing Shalat Dhuha, doing Shalat punctually, implementing the readings and invoking after shalat, greeting firstly when meeting other people, buying the goods as needed and saving. Having a habit to read the book in the spare time and showing the active behaviour in the class.